A Pilot Study of the Views of General Practitioners Regarding Exercise for the Treatment of Depression. Issue 4 (13th October 2014) - Stanton, Robert; Franck, Chris; Reaburn, Peter; Happell, Brenda
<x xml:space="preserve">Abstract</x> Purpose To investigate the views of general practitioners (GPs) regarding exercise and the treatment of depression. Design and Methods Twenty GPs completed a 25‐item survey investigating their knowledge, beliefs, perceived benefits and barriers, and recommendations to patients regarding exercise for the treatment of depression. The exercise habits of the GPs were also recorded. Findings GPs are positive toward exercise in the treatment of depression despite low levels of confidence in prescribing exercise or limited measurable benefits. Exercise patterns of GPs were not associated with GP exercise prescription habits. Practice Implications Education, use of support materials and referral schemes, and increasing exercise behavior among GPs may increase the use of exercise as treatment for people with depression.